'Your mascara is running'. (1st March 2022) - Kelly, A.; Gandhi, R.; Natkunarajah, J.
Abstract: Chromhidrosis is a rare disorder, which can have significant psychosocial consequences for patients, particularly when it affects the face, as it can be mistaken for scarring, dirt or erroneous make‐up application. Chromhidrosis can be divided into apocrine, eccrine and pseudo subtypes. We present a case of apocrine chromhidrosis localized to the bilateral cheek area. Click https://www.wileyhealthlearning.com/#/online-courses/9c761d0a-20de-4709-a57d-36be93cf64e1 for the corresponding questions to this CME article.